Ecophysiological Responses to Rainfall Variability in Grassland and Forests Along a Latitudinal Gradient in Italy - Conte, Adriano; Fares, Silvano; Salvati, Luca; Savi, Flavia; Matteucci, Giorgio; Mazzenga, Francesco; Spano, Donatella; Sirca, Costantino; Marras, Serena; Galvagno, Marta; Cremonese, Edoardo; Montagnani, Leonardo (Frontiers in Forests and Global Change, 2019)
In the Mediterranean region, ecosystems are severely affected by climate variability. The Italian Peninsula is a hot spot for biodiversity thanks to heterogeneous landscape and Mediterranean, Continental, and Alpine climates hosting a broad range of plant functional types along a limited latitudinal range from 40' to 46' N. In this study we applied a comparative approach integrating descriptive statistics, time series analysis, and multivariate techniques to answer the following questions: (i) do the climatic variables affect GPP, Reco, WUE and ET to a similar extent among different sites? (ii) Does a common response pattern exist among ecosystems along a latitudinal gradient in Italy? And, finally (iii) do these ecosystems respond synchronically to meteorological conditions or does a delayed response exists? Six sites along a latitudinal, altitudinal and vegetational gradient from semi-arid (southern Italy) to a mountainous Mediterranean site (central Italy) and sub-humid wet Alpine sites (northern Italy) were considered. For each site, carbon and water fluxes and meteorological data collected during two hydrologically-contrasting years (i.e. a dry and a wet year) were analysed. Principal Component Analysis was adopted to identify temporal and spatial variations in Gross Primary Productivity (GPP), Ecosystem Respiration (Reco), Water Use Efficiency (WUE) and Evapotranspiration (ET). The model outlined differences among Mediterranean semi-arid, Mediterranean mountainous, and Alpine sites in response to contrasting precipitation regimes. GPP, Reco, WUE and ET increased up to 16, 19, 25 and 28 %, respectively in semi-arid Mediterranean sites and up to 15, 32, 15 and 11%, respectively in Alpine sites in the wet year compared to the dry year. Air temperature was revealed to be one of the most important variables affecting GPP, Reco, WUE and ET in all the study sites. While relative air humidity was more important in southern Mediterranean sites, global radiation was more significant in northern Italy. Our work suggests that a realistic prediction of the main responses of Italian forests under climate change should also take in account delayed responses due to acclimation to abiotic stress or changing environmental conditions.